The urgency of personalist bioethics in environmental care - Mendoza Luna, Milagritos Yoelia (2022)
The present work was developed through a bibliographic review of essays and scientific articles, with the purpose of demonstrate that personalist bioethics from its beginnings has been committed to promote the health and the common good, which is also reflected in the ecosystems surveillance balance. So, in the face to the actual environmental problems, it hasn’t been indifferent and the contribution in three areas is highlighted: environmental justice, eco-pedagogy and climate change. Also, personalism is clear about the commitment to nature, because the physical environment is where the person lives and from which he lives to satisfy his needs. Therefore, you must take advantage of the environment with care and responsibility. Given this, ecology with personalist bioethics are a necessary approach for a consumerist society. Thanks to the interdisciplinarity of personalist Bioethics, it has allowed to approach the environmental conflicts in an integrated way identifying although the involved agent’s inequality environmental situations with relation to some people, allowing to assume a responsibility in favor of environmental justice. Likewise, it has contributed to the attitudes changing through awareness of environmental problems such as climate change and through environmental education or Eco pedagogy in university students, for this reason it’s of the utmost importance that in all education levels, from basic to university with the purpose to promote the development of an environment culture in favor of a natural environment.